2020
DOI: 10.1111/1753-6405.13037
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with patterns of psychological distress, alcohol use and social network among Australian mineworkers

Abstract: Objective: To investigate the convergence of individual findings relating to psychological distress, alcohol use and social network (SN) to identify their associated clusters within Australian mineworkers. Methods: This study used cross-sectional survey data from 3,056 participants across 12 Australian mines. Latent class analysis used the scores of Kessler Psychological Distress Scale, Alcohol Use Disorders Identification Test (AUDIT) and Social Network Index. Results: Class 1 (moderate to very high psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
6
1
1
Order By: Relevance
“…Our study showed that 26.4% of the FIFO workers self-reported as current smokers. This is comparable to the findings previously published among FIFO workers (Joyce et al 2013 ) and the general mining workers (James et al 2020 ) in Australia. These rates are higher than the 11.6% reported among adults in Australia (Australian Institute of Health and Welfare 2021b).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed that 26.4% of the FIFO workers self-reported as current smokers. This is comparable to the findings previously published among FIFO workers (Joyce et al 2013 ) and the general mining workers (James et al 2020 ) in Australia. These rates are higher than the 11.6% reported among adults in Australia (Australian Institute of Health and Welfare 2021b).…”
Section: Discussionsupporting
confidence: 91%
“…FIFO work-related characteristics are associated with health issues (Vojnovic et al 2014b ). For instance, studies have demonstrated shift length (Bowers et al 2018 ; James et al 2018 ), e.g., working shifts of more than 12 h (James et al 2018 ), roster patterns, e.g., 2 weeks on/1 week off (Bowers et al 2018 ) and day/night shift rotation (James et al 2020 ) as predictors of high psychological distress among FIFO workers in Australia. Shift patterns (day and night shift) (Asare et al 2021a , b ; Parkes 2012 ) and working longer shift hours (Parkes 2015 ) have also been identified to be linked to reduced sleep duration and poorer sleep quality in FIFO workers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously documented that shift workers’ overall diet quality is poorer than their counter parts, with an increased reliance on nutrient poor, energy dense foods as well as increased snacking frequency [ 47 ]. Considering 80.1% of the participants in this study worked shifts, which is common practice in mining [ 13 , 48 ], it is not surprising to see poorer health outcomes in study participants including elevated BMI, higher consumption of fast food and SSB, as well as inadequate intake of fruit and vegetables. With regards to elevated BMI and shift work status, the significant association within our study mirrors a sentiment which has been reported elsewhere in the literature [ 49 51 ], and more specifically to Australian men [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 (2)-4.Cohort studies in Ishinomaki City, Miyagi Prefecture The Health and Life Revival Council in Ishinomaki District conducted cross-sectional household surveys, highlighting the importance of economic factors for the affected communities and emotional support, especially for the elderly disaster victims. 24,25 The National Center for Global Health and Medicine conducted city-wide longitudinal surveys of kindergarten, elementary school, and junior high school children, observing the recovery course of traumatic symptoms. [26][27][28][29][30][31] The Department of Health Informatics and Public Health, Tohoku University School of Public Health, conducted longitudinal surveys of the residential registry for Ajishima, Ogatsu, Oshika, and Ishinomaki City, as well as residents who were living in prefabricated temporary housing in Wakabayashi-ku, Sendai City, and Miyagi Prefecture.…”
Section: Clinical Neurosciencesmentioning
confidence: 99%
“…The Health and Life Revival Council in Ishinomaki District conducted cross‐sectional household surveys, highlighting the importance of economic factors for the affected communities and emotional support, especially for the elderly disaster victims 24,25 . The National Center for Global Health and Medicine conducted city‐wide longitudinal surveys of kindergarten, elementary school, and junior high school children, observing the recovery course of traumatic symptoms 26–31 …”
Section: Advances In Mental Health Disaster Response After the Gejementioning
confidence: 99%